SEDIMENT FLUXES, NATURAL FILTERING, AND SEDIMENTARY SYSTEMS OF A "LIVING OCEAN" - Lisitzin A.P. (My University, 2004)
A new concept of a "living ocean" is based on thousands of analyses of suspended particulate matter from all oceans, in situ studies of particle fluxes and sedimentation rates, and mass estimates of present and past (in cores) bottom fill. The reported results show that sediment input from rivers is dramatically reworked in the living ocean by plankton and benthos. At the first stage, ~ 93% of material (world average) is captured in marginal river/sea filters; outside the marginal filters, elements, including hydrolysates, exist mostly in the dissolved form. Abundant phytoplankton transforms the soluble elements that penetrate through the filters into suspended matter (biological pump 1), and zooplankton organisms then filter it out from water and aggregate into pellets to transport down to the sea floor (biological pump 2). The pumps 1 and 2 act as filters and chemical barriers at the same time and rework the entire World ocean water volume in six months. The third biological pump - benthos filters, detritus collectors, and mud eaters - acts as fast and terminates the biological rework of sediments, to be continued by bacteria in sea floor deposits. Oceanic sedimentation occurs at the account of material supplied from the biosphere, as well as from the atmosphere, the hydrosphere, the cryosphere, and the Earth's interiors, and water-, wind- or ice-borne, or mantle-derived sediments predominate in different environments. Sediment material is produced, transported, and deposited under the effect of biogenic processes, the previously neglected key agent in chemical and physical cycles in the ocean. The reported results of advanced studies of particulate matter from water, air (aerosols), marine and continental ice (cryosols), hydrothermal plumes, and ocean-island volcanoes open up new avenues for revealing the true course of oceanic sedimentation.
Keywords: Particulate flux; biological filter; marginal filter; biological pump; suspended particles; aerosols